2017
DOI: 10.1182/bloodadvances.2017006163
|View full text |Cite
|
Sign up to set email alerts
|

WNT ligands contribute to the immune response during septic shock and amplify endotoxemia-driven inflammation in mice

Abstract: Key Points• Differential expression of WNT ligands in patients with septic shock and a mouse model of endotoxemia correlates with inflammatory cytokines.• WNT ligands and WNT/b-catenin signaling positively regulate lipopolysaccharideinduced proinflammatory cytokines without impairing IL-10. IL-12/23p40 in serum of LPS-challenged mice and cultured splenocytes, whereas IL-10 production remained largely unaffected. Taken together, our data support the conclusion that the concerted action of WNT proteins during se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…However, it is important to note that β-catenin activity in regulatory T cells impairs their functions and drives colitis and tumor development ( 44 , 45 ). Moreover, we recently demonstrated that pharmacologic targeting of both β-catenin activity and Wnt production impaired pro-inflammatory cytokine responses in an endotoxemia model in mice ( 46 ), indicating pro-inflammatory functions of Wnt/β-catenin signaling in this context. Future studies will focus on identifying individual Wnt/Wnt receptor combinations that shape NKT cell functions and fate, as well as the specific cellular sources of the Wnt ligands that regulate cytokine production by NKT cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that β-catenin activity in regulatory T cells impairs their functions and drives colitis and tumor development ( 44 , 45 ). Moreover, we recently demonstrated that pharmacologic targeting of both β-catenin activity and Wnt production impaired pro-inflammatory cytokine responses in an endotoxemia model in mice ( 46 ), indicating pro-inflammatory functions of Wnt/β-catenin signaling in this context. Future studies will focus on identifying individual Wnt/Wnt receptor combinations that shape NKT cell functions and fate, as well as the specific cellular sources of the Wnt ligands that regulate cytokine production by NKT cells.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling has been reported elsewhere to exert the anti-inflammatory or pro-inflammatory properties [35][36][37][38][39]. Indeed, in the intestine the activation of Wnt/beta-catenin pathway helps to maintain GVB function [2,34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their roles in inflammation, recent studies have reported that these Wnt ligands play key roles in tissue damage and repair [ 6 ]. Interestingly, previous studies have reported significant alterations in Wnt5a and Wnt11 expression compared to other Wnt ligands by analysing sera of patients with severe sepsis or sepsis mouse model [ 4 , 8 ]. Wnt5a signalling has been known to activate in sepsis or ARDS and play a pivotal role in lung inflammation and fibrosis [ 5 , 9 ], whereas Wnt11 protein has been reported to suppress induction of inflammatory cytokines by regulating NF-κB activity [ 10 , 11 ].…”
mentioning
confidence: 99%